Five Eyes Alliance Policy Towards China-Huawei Public-Private 5G Partnerships - Muhammad Fadhlan Firasyan Aclamuf; Yusuf, Dedi; Muhammad Rifqi Naufal; Deniati, Nia; Heryadi, Dudy; Sari, Deasy Silvya (Department of International Relations, Universitas Brawijaya, 2025)
In the transformation of global infrastructure, the emerging 5G technology has become the cornerstone of a digital revolution that has changed the way humans do business and interact with each other. Huawei is one of the Chinese technology companies that has made a name as a global leader in this technology. However, the existence of Public Private Partnership (PPP) between China and Huawei makes western countries, especially countries that join the Five Eyes intelligence alliance feel threatened, especially in their cyber security. This research aims to analyze the Five Eyes policy towards the public private partnership between the Chinese government and Huawei. This research uses the theory of cybersecurity and the concept of Public-Private Partnership as the research analysis framework. This research found that Huawei's launch of 5G technology supported by the Chinese government caused opposition from Western countries that are members of the Five Eyes intelligence alliance. Based on national security reasons, the launch of 5G technology by Huawei and the Chinese government is considered dangerous and is allegedly a strategy of the Chinese government to conduct espionage and other spying activities against countries in the world to fulfill the interests of the country. This triggered the imposition of a ban on Huawei's 5G technology in several countries, including the Five Eyes member countries.